Exploring the Relationship Between Antimicrobial Stewardship and the Rise of Multi-Drug Resistant Pathogens in Healthcare Settings - Javed , Umer; Taj, Naveen; Noor , Isra; Shareef , Tehreem Yaseen; Anees, Hafsa; Khan, Warisha (Indus Journal of Bioscience Research, 2025)
The aim of this study was to examine the relationship between the antimicrobial stewardship (AMS) programs and the relationship between these programs and the incidence of multi-drug resistant (MDR) pathogens within a healthcare facility, and how healthcare practitioners are provoked in administering an AMS program. Multi-drug resistance has been a serious health concern of late with the infections more susceptible to healing and patients are at a higher risk. It was a descriptive cross-sectional research performed in a few out of the total number of the governmental and regional hospitals in the province of Punjab in Pakistan during the period between March 1, 2025 and May 15, 2025. A sample of 250 healthcare professionals, was chosen by simple random sampling. A structured questionnaire with self-report was used to carry the observation and measurements. Frequencies and percentages were used to report categorical data whereas the means and standard deviation (SD) were used to report numerical data. Associations and Comparing of Means were performed on chi-square and Independent Samples t-tests. The results showed a high correlation in use of AMS and the incidences of MDR (p = 0.003) with few MDR cases per hospital having AMS implemented to practice. The knowledge of AMS was significantly higher in the case of the public hospitals when compared to those in a private hospital (p = 0.014). There were higher scores of challenges in AMS implementation among nurses and the pharmacists. The results indicate that there is a need to enhance AMS programs.